Optimization of the formulation of canned anchovy (Engraulis ringens J.) in gourmet sauce by sensory evaluation - Pantoja Tirado, Lucia Ruth (2022)
The anchovy (Engraulis ringens J.) is a species distributed in differentiated ecosystems around the world, being one of the most exploited today in Peru. The main objective of this work was to determine the optimal formulation of a canned anchovy in gourmet sauce by sensory evaluation, prepared based on the use of Cushuro (Nostoc sphaericum, Vaucher ex Bornet & Flahault), Sacha Inchi oil (Plukenetia volubilis L.), Chincho (Tagetes elliptica Sm.), Rosemary (Salvia rosmarinus L.) and Potato (Solanum tuberosum L.). A 32 factorial design was used, where sacha inchi oil concentrations (3, 5.5 and 8%) and cushuro, concentrations (7, 9.5 and 12%), represented the two factors. The sensory evaluation was carried out with 50 semi-trained panelists, of both sexes and with different ages. The general acceptability method was used, evaluating the treatments on a continuous scale, considering the smell, taste, texture, appearance, color and general acceptability sensory variables. The best formulation consisted of 8% Sacha Inchi oil, 12% Cushuro, 6% mother sauce and the rest of the ingredients with standard values for all formulations, also presenting the highest nutritional levels and adequate content of omega oils 3, 6 and 9. The sugar, sodium, saturated fats and trans fats contents in the optimal formulation were below the maximum values established by Law in Peru. The canned anchovy in gourmet sauce was a commercially sterile product, suitable for human consumption.